WACANA SYARIAT KONTEMPORER DI BARAT: Studi Pemikiran Wael B. Hallaq dan M. Barry Hooker - Nasir, Mohamad Abdun (ULUL ALBAB Jurnal Studi Islam, 2017)
Contemporary popular discourses about Islam, shariâ€™a and Islamic law in the West is often filled with the issues of terrorism, anti-democracy, human rights violation and womenâ€™s minor status in Islam, which all lead into negative perception. Unlike such popular views, Western scholars perceive shariâ€™a from various perspectives. They are quite critical to shariâ€™a in a positive sense. This article discusses Western scholarly discourses on shariâ€™a by comparing the thoughts and works of two most prominent figures, Wael B. Hallaq and M. Barry Hooker, who always concern with shariâ€™a, Islamic law and related social issues, such modernity, colonialism and legal system. Based on the model of the study of public figure and grounded its main data on Hallaqâ€™s and Hookerâ€™s main work, this study shows that these two scholars promote idealistic and contextual perception on shariâ€™a. From the ideal point of view, shariâ€™a is seen a product of scholarly independent work by Muslim jurists, whose authority now is unfortunately taken over by the state. The contextual view regards shariâ€™a as flexible Islamic religious or legal norms that are adaptable to the changing social and political environments so they are easily transferrable into the educational, legal and political system in a country like Indonesia, entailing what is called â€œnational mazhabâ€.